Education Policies and the Restructuring of the Educational Profession Global and Comparative Perspectives (Perspectives on Rethinking and Reforming Education,, 2018)
The book analyzes worldwide changes in school organization and the teaching profession, and how the profession has been impacted by education policies that promote assessments and accountability. It also identifies some shifts in professional positions, statuses and profiles, and characterizes the impact and contextualization of professional standards that shape teaching practices and the management of schools. Further, the book provides relevant comparative and empirical data on the restructuring of the teaching profession in an era of globalization through a critical perspective on and an overview of the main research and comparative findings across countries. As such, the book is not only directed to educational researchers but will also interest professionals and policymakers, addressing a broader education and policy community concerned by the new aspects shaping the teaching profession in the 21st century.